2023
DOI: 10.1111/cdoe.12846
|View full text |Cite
|
Sign up to set email alerts
|

Education‐related inequalities in oral health among older adults: Comparing Singapore and Japan

Abstract: Objectives Oral health inequalities exist worldwide, and cross‐country comparisons can provide valuable insights into country‐level characteristics contributing to such inequalities. However, comparative studies in Asian countries are limited. This study examined the magnitude of education‐related oral health inequalities in older adults in Singapore and Japan. Methods Longitudinal data for older adults, aged ≥65 years, from the Panel on Health and Ageing of Singaporean Elderly (PHASE; 2009, 2011–2012, and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…", and participants chose "19 or fewer teeth" or "20 or more teeth". Previous studies have reported that having 20 or more teeth was considered to have sufficient masticatory function [24,25]. The inquiry regarding gum bleeding was as follows: "Do you have bleeding gums while brushing your teeth?".…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…", and participants chose "19 or fewer teeth" or "20 or more teeth". Previous studies have reported that having 20 or more teeth was considered to have sufficient masticatory function [24,25]. The inquiry regarding gum bleeding was as follows: "Do you have bleeding gums while brushing your teeth?".…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…Despite this evidence, there has been limited research on the implications of health inequalities for crucial indicators of older people's health, such as geriatric syndromes, which, due to their complexity and interrelationships, substantially impact how we age. For instance, a recent study examined the magnitude of oral health inequalities among older people using longitudinal data from Japan and Singapore, reporting that oral health inequalities increased over time in both countries, but mainly in Singapore ( Kiuchi et al, 2023 ). Nevertheless, studies on health inequalities with older adults have been primarily cross-sectional, and the results have shown that frailty, depression, functional limitations, chronic conditions, falls, low muscle mass, and cognitive impairment are concentrated in older people with a disadvantaged socioeconomic level ( Azizabadi et al, 2022 ; Katikireddi et al, 2020 ; Makaroun et al, 2017 ; Salinas-Rodríguez et al, 2019 ; Saravanakumar et al, 2022 ; Shang & Wei, 2023 ; Sharma & Pradhan, 2023 ; Tsimbos, 2010 ).…”
Section: Introductionmentioning
confidence: 99%